Sosialisasi Pengolahan Sampah Organik Menggunakan Maggot BSF Di Desa Sembalun Timba Gading Kecamatan Sembalun Lombok Timur - Syamsuhaidi Syamsuhaidi; Dwi Kusuma Purnamasari; Erwan Erwan; Sumiati Sumiati; K.G. Wiryawan; V. Maslami; Moh. Taqiuddin (Universitas Mataram, 2023)
Community service activities aim to socialize kitchen organic waste management that can be done at the household level. This socialization activity was carried out at the request of a village youth leader who hoped to solve the problem of the accumulation of vegetable and fruit waste in Sembalun Timba Gading Village. The targets of community service activities are youth leaders, community leaders, and village officials. The socialization of organic waste management begins with dissemination of sorting kitchen organic waste (s.o.d) and continues with socialization on processing s.o.d. using the Black Soldier Fly (BSF) maggot. This processing technology will solve the problem of household waste and unsold vegetable and fruit waste and increase people's income by producing products in the form of commercial maggot and used maggot (kasgot). Maggot products can be used as poultry and fish feed, while cassava can be used as organic fertilizer for rice fields, plantations and horticultural crops. The socialization activity was enthusiastically attended by village administrators and youth of Sembalun Timba Galih Village (about 25 people). Service participants will follow up on this activity by making a proposal for a training program for organic waste processing using BSF maggot in order to create environmental cleanliness in tourist areas such as Sembalun Timba Gading Village. Community service activities resulted in an increase in knowledge, attitudes, and enthusiasm for the administrators and youth of Sembalun Timba Gading Village in solving waste problems and committed to working together synergistically with academics to carry out organic waste management training in the next Sembalun Timba Gading Village.